Factors influencing prevention and control of malaria among pregnant teenagers in rural parts of Delta State, Nigeria - Rolle Remi Ahuru; Clement Atewe Ighodaro (Wolters Kluwer Medknow Publications, 2021)
This study was conducted to assess the factors associated with malaria prevention and control among pregnant teenagers in four Primary Healthcare Centers in rural Delta State. A facility-based cross-sectional study was conducted among 427 pregnant teenagers in the rural part of Delta State, and data were collected using a self-administered questionnaire prepared in English and analyzed using STATA 13.0. Descriptive statistics and binary logistic regression analysis were conducted to determine the prevalence of malaria adherence and its predictors among pregnant teenagers. The results revealed that 50.1% reported sleeping under insecticide-treated nets (ITNs), 49.2% reported using indoor residual spray (IRS), and 38.4% intermittently treat malaria in pregnancy (IPTp). Women who reported secondary educational qualification were approximately three times (adjusted odd ratio [aOR]: 2.72, P =0.01), five times (aOR: 5.27, P <0.001) and nine times (aOR: 9.23, P <0.001) significantly and respectively more likely to sleep under ITNs, use IRS and IPTp. Those who reported tertiary education (aOR: 6.16, P =0.04) were approximately six times significantly more likely to IPTp. Unemployed women (aOR: 0.46, P =0.02) were 54% significantly less likely to intermittently treating malaria in pregnancy. The findings suggest that malaria prevention programs and intervention strategists should consider the socioeconomic conditions of poor rural teenagers, promote female literacy, and target women with several births.